Neuroblastoma: Analysis of a case in an adolescent - Castelli, Fernando; Maglione, Oscar; Caviglia, Pablo (Cirugía del Uruguay, 2004)
A 19 year old adolescent presented a suprarenal neuroblastoma. This led to a revision of disease. lt is basica/ly found in infants and newborns, but may appear in adolescents and adults. lts prognosis is poor the older the patient, al/ the worse. Treatment is fundamental/y chemo- and radiotherapy and surgery is reserved far diagnosis or total excision of the rare non-disseminated cases or in arder to decrease the size of mass of a/leviate compressive symptoms.